Clusters and Graphs: Revealing and Modeling Documentary Indefiniteness. - Fox, Michael (Textual Cultures: Text, Contexts, Interpretation (Society for Textual Scholarship))
The documentary record of interrelated, multimedia literary works is riddled with indefiniteness. The order of their materials is often uncertain, as is the medium that should serve as their point of reference. This article argues that such common and related indefiniteness, like ambiguity and genetic lineage, whether revealed through traditional scholarly methods or computational ones, can be modeled using graph technology. Graph technology, moreover, can be used to model much more about these literary works, from their atomic documentary features to their higher-order features. The article uses as its example Jaime de Angulo's Old Time Stories, a Modernist American masterpiece consisting of voice, text, and image. Graph modeling, or graph editing, the work results in a fine-grained, computationally accessible representation of it as it really is in all its indefinite and networked nature. Such a representation lends itself to typical hermeneutic investigations enhanced by the power of inferential queries, and it can even serve as an actually authentic source for more quantitative investigations. Most important, like all non-digital natural-language based artifacts, it can also be endlessly modified by future editors without ever giving up from its structure the history of its own making.